Horizontal transfer of a pathway for coumarate catabolism unexpectedly inhibits purine nucleotide biosynthesis. Issue 6 (1st October 2019) - Close, Dan M.; Cooper, Connor J.; Wang, Xingyou; Chirania, Payal; Gupta, Madhulika; Ossyra, John R.; Giannone, Richard J.; Engle, Nancy; Tschaplinski, Timothy J.; Smith, Jeremy C.; Hedstrom, Lizbeth; Parks, Jerry M.; et al.
Summary: A microbe's ecological niche and biotechnological utility are determined by its specific set of co‐evolved metabolic pathways. The acquisition of new pathways, through horizontal gene transfer or genetic engineering, can have unpredictable consequences. Here we show that two different pathways for coumarate catabolism failed to function when initially transferred into Escherichia coli . Using laboratory evolution, we elucidated the factors limiting activity of the newly acquired pathways and the modifications required to overcome these limitations. Both pathways required host mutations to enable effective growth with coumarate, but the necessary mutations differed. In one case, a pathway intermediate inhibited purine nucleotide biosynthesis, and this inhibition was relieved by single amino acid replacements in IMP dehydrogenase. A strain that natively contains this coumarate catabolism pathway, Acinetobacter baumannii, is resistant to inhibition by the relevant intermediate, suggesting that natural pathway transfers have faced and overcome similar challenges. Molecular dynamics simulation of the wild type and a representative single‐residue mutant provide insight into the structural and dynamic changes that relieve inhibition. These results demonstrate how deleterious interactions can limit pathway transfer, that these interactions can be traced to specific molecular interactions between host and pathway, and how evolution or engineering can alleviate these limitations. Abstract : A pathway for catabolism of coumarate, a biotechnologically relevant lignin‐derived aromatic compound, was engineered into Escherichia coli . Accumulation of an intermediate, 4‐hydroxybenzaldehyde, was shown to inhibit a key enzyme in purine nucleotide biosynthesis, IMP dehydrogenase (IMPDH). Inhibition could be relieved through point mutations to IMPDH that altered enzyme dynamics without disrupting the catalytic center.